Actitud de los padres de familia frente al desarrollo psicomotor de los niños y niñas con parálisis cerebral espástica, en el centro de atención y desarrollo de niños y niñas especiales CADE. Año lectivo 2012 - 2013 - Tituana Tituana, Nuvia Cristina (2013)
The present thesis makes reference to the ATTITUDE OF THE PARENTS OF FAMILY In front of THE PSYCHOMOTOR DEVELOPMENT OF THE CHILDREN AND GIRLS WITH CEREBRAL SPASTIC PARALYSIS, IN THE CENTER OF ATTENTION AND DEVELOPMENT OF CHILDREN AND SPECIAL GIRLS "CADE." YEAR LECTIVO 2012 – 2013. Elaborated according to the regulation of the National University of Loja. A general objective was formulated that was: To make aware the parents of family of the importance that he/she has their attitude in front of the psychomotor development of the children and girls with cerebral spastic paralysis. The methods used for the preparation of this research work were: Scientist, Analytical - Synthetic, Inductive - Deductive, Descriptive, Statistical Model, Techniques and Tools were: Survey applied to evaluate the different attitudes that parents have against its children. Motor Ability Test of Oseretzky, applied to assess psychomotor development with children's center "CADE". According to the instruments applied to the educational ones they manifested that: 32% of the children is rejected by its parents, 26% says that it feels guilty, 21% manifests to be persevering, 16% informs that they feel shame, and alone 5% they manifested that they accept them with its deficiency. These attitudes present the family parents in front of the disabilitiesof their children fearing inspiring pity, fear to receive critical and it deceives of the other ones; shame of being exposed to the look of the society in general. Regarding the Ability Test Oseretzky Powertrain: 100% of children who are Oserestzky apply the test were viewed Unsatisfactory Coordination in Static; 100% in the speed, accuracy, strength and balance was not satisfactory in 93% accuracy Movements, unsatisfactory, 7% satisfactory, 92% in the dynamic Coordination was not satisfactory and 8% satisfactory, 92% in the speed of movements was unsatisfactory and 8% satisfactory, 92% in the simultaneous movements unsatisfactory and 8% satisfactory. In children with cerebral palsy usually seen various psychomotor development disorders caused by poor knowledge they have of their body, incorrect use or altered perception of the same.